The Effect Of Return On Assets, Debt-To-Equity Ratio, And Total Asset Turnover On Price-To-Book Value In Non-Cyclical Consumer Sector Companies Listed On IDX For The 2021-2025 Period - Edelweiss Eleanor; Santi Damayanti; Diah Febriyanti; Kartika Berliani (CV Putra Publisher, 2026)
This study examines the empirical impact of Return on Assets (ROA), Debt-to-Equity Ratio (DER), and Total Asset Turnover (TATO) on Price-to-Book Value (PBV). Using a purposive sampling approach, this study identified 48 Consumer Non-Cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the observation period from 2021 to 2025. This research adopted a quantitative method, and the analysis was based on secondary data collected from the companies' annual financial reports. Through descriptive statistics, classical assumption tests, multiple linear regression, the coefficient of determination, and hypothesis testing, the results indicated that the combination of ROA, DER, and TATO had a significant effect on PBV. In contrast, partial analysis showed different dynamics; while ROA and DER showed a significant partial effect, TATO did not reach statistical significance independently. Furthermore, the explanatory power of this framework is reflected in an adjusted R-squared (R2) of 0.473, implying that 47.3% of the variance in PBV is driven by these three independent predictors. The remaining 52.7% is due to external factors not included in the current estimation model